2020
DOI: 10.3390/ijms21186969
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence of Antidepressant Effects of Insulin and Anti-Hyperglycemic Agents and Implications for the Pathophysiology of Depression—A Literature Review

Abstract: Close connections between depression and type 2 diabetes (T2DM) have been suggested by many epidemiological and experimental studies. Disturbances in insulin sensitivity due to the disruption of various molecular pathways cause insulin resistance, which underpins many metabolic disorders, including diabetes, as well as depression. Several anti-hyperglycemic agents have demonstrated antidepressant properties in clinical trials, probably due to their action on brain targets based on the shared pathophysiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 232 publications
0
15
0
Order By: Relevance
“…glucagon-like peptide 1 receptor agonists and dipeptidyl peptidase 4 inhibitors), might also improve cerebral microvascular function and have neuroprotective effects through non-lipid and non-glucose pathways. Small trials and observational studies (119)(120)(121)(122) suggest that these drugs may lower depressive symptoms. In addition, several trials are being done to evaluate the effect of statins (e.g.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…glucagon-like peptide 1 receptor agonists and dipeptidyl peptidase 4 inhibitors), might also improve cerebral microvascular function and have neuroprotective effects through non-lipid and non-glucose pathways. Small trials and observational studies (119)(120)(121)(122) suggest that these drugs may lower depressive symptoms. In addition, several trials are being done to evaluate the effect of statins (e.g.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Among them, serotonin drug Agomelatine significantly reduced the scores of depression and anxiety at the end of the treatment of depression caused by type 2 diabetic comorbidities ( Norman and Olver, 2019 ). Anti-hyperglycemic such as Insulin and Anti-Hyperglycemic Agents, which agents have demonstrated antidepressant properties in clinical trials, probably due to their action on brain targets based on the shared pathophysiology of depression and T2DM ( Woo et al, 2020 ). In addition, there are tricyclic antidepressants, monoamine oxidase inhibitor, atypical antidepressants, and some traditional Chinese medicine antidepressants ( Zhang X. et al, 2017 ).…”
Section: Clinical Therapeutic Intervention Strategymentioning
confidence: 99%
“…Disturbances in blood sugar regulation, insulin concentrations, and insulin resistance have been identified in depression [ 173 , 174 ]. Although the administration of antihyperglycaemic agents, including metformin and peroxisome proliferator-activated receptor-γ (PPARγ) receptor agonists, have yielded inconsistent findings in depression studies, insulin signalling has been shown to influence serotonergic transmission [ 173 , 174 ]. Based on a meta-analysis of four trials and 453 participants, it was concluded that curcumin supplementation may assist in improving insulin resistance and glycaemic control [ 175 ].…”
Section: Curcumin’s Potential Antidepressant Mechanisms Of Actionmentioning
confidence: 99%